The Situation of Persons with Disabilities on The Labour Market in Poland And Other Countries During The COVID-19 Pandemic - Andrzej KOZA; Adriana POLITAJ (Communications of International Proceedings, 2021)
The aim of this article is an attempt to analyze the changes taking place on the labour market in Poland and other countries during the COVID 19 pandemic. Particular attention focused on situation of people with disabilities. These people are commonly considered to be at risk of social exclusion mainly due to unemployment. Therefore, the authors decided to look at how effective the state's actions aimed at protecting employers and jobs were proved. The motivation to undertake research in this area was the experience from the period of the global financial crisis in 2007-2008, as a result of which many employers went bankrupt and unemployment increased. People with disabilities at that time were in a particularly difficult situation. Therefore, the authors decided to check whether the current global crisis caused by the COVID-19 pandemic will have similar negative effects on the labor market, especially among people with disabilities. The article presents a descriptive and comparative analysis based on the studies covering the leading world literature and statistical data. The research timeframe covered 2019-2020, due to the significant transformations occurring on Polish labour market and the availability of consistent and revised statistical data.
Keywords: COVID -19 pandemic; disability; unemployment; employment